The state with lowest sex ratio in India: role of socio – cultural factors? - Jangra, Babita; Alla, Sonali; Majra, Jaipal (International Journal Of Community Medicine And Public Health, 2017)
Background: Child sex ratio is declining rapidly from 945 in census 2001 to 927 in census 2011.With the average family size decreasing rapidly and preference for male child remaining the same, the female child population is showing a downward trend. Objectives: To study the factors responsible for low child sex ratio and to study the relationship between sex ratio and birth order. Methods: The study was done in Primary health centre, Khanpur Kalan which is rural field practice area attached to the department of community medicine, BPS Govt. Medical College for women, Khanpur Kalan, Sonepat, Haryana. Assuming the probability of being born as female is 50%, the calculated sample size was taken as 400 at 95% confidence interval. Data was collected from house to house visit with the help of pre tested and semi structured questionnaire. Results: The overall child sex ratio of the study population was 620. Sex ratio goes on decreasing with increasing educational status of parents and with increasing birth order. Most common factor responsible for girl child negligence as told by respondents is domestic violence and ill treatment by husband and in laws. The most common reason for male child preference as told by the respondent is to run the family name, followed by security in old age and to perform the last rites. Conclusions: There should be National Policy for giving social security and equal rights to females so that parents do not feel any type of social or financial insecurity. Monitoring and counselling of families especially the families with previous two girls should be done at the community level.